An Ayurvedic herbal extract inhibits oral epithelial cell IL-8 responses to host and bacterial agonists - Chang, Ana M. (BMC Complement Med Ther, 2020)
BACKGROUND: Natural products constitute a promising class of therapeutics for the treatment of gingivitis and periodontitis as well as the maintenance of oral health. However, the limited understanding behind their potential mechanisms and modes of action have hampered their incorporation into popular western therapeutics. This in vitro study characterizes an Ayurvedic herbal extract mixture, which has been clinically shown to promote gingival health and homeostasis. METHODS: Telomerase immortalized gingival keratinocytes (TIGK) were infected with either Fusobacterium nucleatum cell wall, live F. nucleatum, IL-1β or TNF-α for 4 hours with and without the herbal extract. The immunomodulatory effects of the extract on host IL-8 production was measured by ELISA. RESULTS: It was found that the Ayurvedic herbal extract mixture inhibited gingival epithelial cell IL-8 expression in response to both bacterial and host cytokine agonists. The herbal extract inhibited IL-8 stimulated by F. nucleatum cell wall, live F. nucleatum, IL-1β, and TNF-α in a dose-dependent manner that was not a result of host cell death. Furthermore, the extract showed significantly different ID(50) doses demonstrating the differential ability to modulate both stimulated and basal IL-8 levels. CONCLUSIONS: In vitro investigation of this herbal extract mixture revealed that it has the ability to modulate gingival epithelial cell IL-8 expression in response to stimulation by bacterial components and host pro-inflammatory signals. This data demonstrates that the reduction in the gingival epithelial cell IL-8 response may in part be responsible for the previously reported ability of the Ayurvedic herbal extract mixture to reduce gingivitis in two separate human clinical studies.